Cover Feature: Rhodium(I) Complexes of N‐Aryl‐Substituted Mono‐ and Bis(amidinates) Derived from Their Alkali Metal Salts (Eur. J. Inorg. Chem. 26/2018). Issue 26 (15th June 2018) - Moos, Eric M. B.; González‐Gallardo, Sandra; Radius, Michael; Breher, Frank
Abstract : The Cover Feature shows a strategy to modify the metal‐metal distance in dinuclear rhodium(I) complexes based on linker‐bridged bis(amidinate) ligands. As part of the collaborative research center3MET, our group aims at understanding the underlying principles governing cooperative effects in catalysis. To rationally synthesize polynuclear complexes with tuneable metal–metal distances, a series of chelating N‐donor ligands was developed, which would concomitantly have an influence on possible cooperative effects. More information can be found in theFull Paper by F. Breher et al.